Efficient one step extraction process of Gramicidin S from Aneurinibacillus aneurinilyticus biomass - Lvova, Ksenia; Vecino, Xanel; Pérez-Cid, Benita; Moldes, Ana B.; Cruz, José M. (Frontiers in Bioengineering and Biotechnology, 2024)
Currently, Gramicidin S (GR-S) is produced enzymatically with the drawback of the presence of trifluoroacetic acid (TFA) or produced by fermentation involving several separation and purification steps. Therefore, this study is focused on the use of green solvents as unique extraction step to produce Gramicidin S from microbial biomass of Aneurinibacillus aneurinilyticus. Among the tested solvents, such as ethanol, acidic ethanol or buffer phosphate, the most favorable was acidic ethanol, extracting 96 % of Gramicidin S from cells with a purity of 90 %. Using acidic ethanol, extraction time within the range of 30-120 minutes exhibited minimal impact on Gramicidin S yield, whereas the biomass-to-extractant ratio emerged as a critical parameter.Gramicidin S extracts were characterized using Fourier Transform Infrared Spectroscopy (FTIR), Matrix Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF-MS), and Electrospray Ionization Mass Spectrometry (ESI-MS) coupled with Ultra Performance Liquid Chromatography (UPLC) and compared with commercial Gramicidin S.